The Republic of Croatia : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2012)
Staff Report for the 2012 Article IV consultation, prepared by a staff team of the IMF, following discussions that ended on October 2, with the officials of Croatia on economic developments and policies. Based on information available at the time of these discussions, the staff report was completed on October 23. The views expressed in the staff report are those of the staff team and do not necessarily reflect the views of the Executive Board of the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet